2021
DOI: 10.1108/itp-06-2019-0285
|View full text |Cite
|
Sign up to set email alerts
|

Understanding post-adoption behaviour in the context of ride-hailing apps: the role of customer perceived value

Abstract: PurposeDespite the perceived role of customer value in post-adoption behaviour in the context of ride-hailing apps such as Uber, there has been limited research on the subject. This paper seeks to enrich the understanding of the relationships between customer perceived value, particularly hedonic value and economic value, customer satisfaction and continued use intentions of ride-hailing apps.Design/methodology/approachThis analysis is based on field data collected from 567 users of ride-hailing apps in Ghana.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…Satisfaction is a customer’s positive affective response due to their appraisal of a product/service (Cheng et al , 2018). Customer behaviour after the adoption of an innovation depends on satisfaction with past experiences (Ofori et al , 2022). Satisfactory experiences enhance continuance intention, whereas dissatisfactory experiences impede intention to reuse (Lee and Kim, 2018).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Satisfaction is a customer’s positive affective response due to their appraisal of a product/service (Cheng et al , 2018). Customer behaviour after the adoption of an innovation depends on satisfaction with past experiences (Ofori et al , 2022). Satisfactory experiences enhance continuance intention, whereas dissatisfactory experiences impede intention to reuse (Lee and Kim, 2018).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Customer satisfaction is mentioned as a basic determinant of loyalty intention in the previous literature (Cheng et al, 2018; Ofori et al, 2021; Oghuma et al, 2016). Particularly, in the ECM, customers' satisfaction is considered to be a necessary condition for development that directly affects customer continuance intention (Bhattacherjee, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheng et al (2018) examine antecedents influencing online and offline service quality toward a sharing economy car‐hailing service, pointing out relationships between service quality, satisfaction, and loyalty. In addition, Ofori et al (2021) revealed that customer satisfaction significantly affects the continued use intentions of ride‐hailing apps. Based on the above arguments, it is reasonable to propose the following:H3 Customers' satisfaction value is positively associated with their retention on STA .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with apparent technology advantages, the economic benefits that passengers may obtain from ride-hailing service providers through the applications should be considered when determining customer happiness and loyalty. For instance, Grab, Vietnam's leading transportation service app, has been aggressively discounting and promoting its services recently, including a free ride trial, discount promo code, referral program, and discounts in select areas, in order to keep its existing customers away from emerging services offers from transportation service providers might be conceptualized as perceived sales promotion, which was one of the characteristics of marketing tools that used short-term, non-periodic approaches to increase sales in a variety of ways (Ofori et al, 2021). Furthermore, it was a critical component of the four Ps of the marketing mix, which were used to attract consumers and encourage them to purchase or try their goods and services (Younus et al, 2015).…”
Section: Customer Behavioral Intention and Ride-hailing Service Qualitymentioning
confidence: 99%
“…In the context of ride-hailing, buying intention refers to a consumer's desire to book a trip using the ride-hailing mobile app. Moreover, a positive attitude toward a certain product, brand, or service provider results in a buy intention (Ofori et al, 2021). Once established, such intentions are difficult to reverse, since customers would want to utilize the chosen product, brand, or service provider if they have access to them.…”
Section: Customer Behavioral Intention and Ride-hailing Service Qualitymentioning
confidence: 99%